Neonatal Transfer Rate and Mode of Delivery from 37th Week of Gestation in a German Perinatal Center Level 1 - Reinhard, J.; Hanker, L.; Sänger, N.; Yuan, J.; Louwen, F. (Geburtshilfe und Frauenheilkunde, 2013)
Introduction: Rates for caesarean section are on the rise and the reasons for this are being discussed worldwide. As the data is unclear, the identification of additional predictive factors for caesarean section is important as caesarean sections are closely linked to maternal and neonatal morbidity. The aim of the study was to identify predictive factors for the transfer of the neonate to a neonatal intensive care unit (NICU) depending on the mode of delivery. The study investigated the neonatal transfer rates for singleton and twin pregnancies delivered at ≥ 36 + 0 weeks of gestation. Material and Methods: The data of all singleton (n = 4181) and twin pregnancies (n = 305 neonates), delivered between 1 January 2009 and 31 March 2012 in the OB/Gyn Department of the University Hospital Frankfurt/M, Germany, (perinatal center level 1) were evaluated. The indications for transfer to the NICU and possible predictive factors were evaluated. Results: Our study found a two times lower neonatal transfer rate for vaginal deliveries of pregnant women without risk factors compared to women with risk factors. The following neonatal transfer rates to the NICU were noted for singleton pregnancies: 4.7 % without risk factors, 8.3 % high-risk pregnancy, 6.2 % vaginal breech delivery, 9.3 % forceps delivery, 10 % elective primary caesarean section and 14 % secondary caesarean section. There was a statistically significant correlation between gestational age and transfer to the NICU (rho 0.11; p < 0.001). Similarly, a correlation was also found for mode of delivery (0.12; p < 0.001), 5 minute APGAR score (0.24; p < 0.001), 10 minute APGAR score (0.34; p < 0.001) and birth weight (0.12; p < 0.001). Conclusion: Vaginal delivery resulted in a lower rate of neonatal transfers compared to caesarean section and the difference was statistically significant. Gestational age had a statistically significant impact on the transfer rate.
Keywords: mode of delivery (caesarean section; forceps; vaginal delivery); vaginal breech delivery; twin; term neonate; transfer rate to neonatal intensive care